Decomposition of Oil Palm Frond and Leaflet Residues - Heru Bagus Pulunggono; Syaiful Anwar; Budi Mulyanto; Supiandi Sabiham (AGRIVITA, Journal of Agricultural Science, 2019)
Frond and leaflet residues from pruning of oil palm which are applied as mulch on oil palm plantation will decompose and can be source of organic matter and some essential nutrients. Information about how much the released nutrients from the decomposition processes of frond and leaflet of oil palm is limited. The objective of this research was to study the period (two years) patterns of nutrient release and decomposition of frond and leaflet of oil palm at different burial depth (0 to 30 cm) in peat soil. Decomposition of frond and leaflet of oil palm did not have a different pattern in mass loss, chemical content changes of C/N, N content, P content, P released, however, it has different pattern in N released. During two years of decomposition, frond and leaflet lost 88% and 86% of its initial weight and released 51% and 83% of N, also it released P 87% and 93% respectively. Frond and leaflet from pruning of oil palm should be returned to plantation area for one source of nutrients beside fertilizer.